2003
DOI: 10.1603/0022-0493-96.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Light Activation of Russian Wheat Aphid-Elicited Physiological Responses in Susceptible Wheat

Abstract: The impact of light and its role in Russian wheat aphid, Diuraphis noxia (Mordvilko), damage symptom formation, and photosynthetic capacity in 'Arapahoe' wheat (Triticum aestivum L.) were examined. After 72 h under continuous dark or continuous light regimes, the number of aphids (nymphs), leaf rolling and chlorosis ratings, fresh leaf weight, and chlorophyll contents were recorded. Photosynthetic rates, chlorophyll a, kinetics and chlorophyll extractions also were determined. Aphid infestation caused signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
1
18
0
5
Order By: Relevance
“…Macedo et al (2003a) reported similar changes in qP and qN and suggested that biochemical mechanisms for restoring chlorophyll to a low energy, light receptive-state, such as quenching, may be more immediately impaired by aphid feeding.…”
Section: Chlorophyll Fluorescence Measurementsmentioning
confidence: 81%
See 2 more Smart Citations
“…Macedo et al (2003a) reported similar changes in qP and qN and suggested that biochemical mechanisms for restoring chlorophyll to a low energy, light receptive-state, such as quenching, may be more immediately impaired by aphid feeding.…”
Section: Chlorophyll Fluorescence Measurementsmentioning
confidence: 81%
“…After aphid removal, the tolerant cultivar demonstrated a complete recovery of photosynthetic capacity, while photosynthetic compensation did not occur in the susceptible or antibiotic cultivars. Macedo et al (2003a) also found that D. noxia infestation on susceptible wheat can cause significant reductions in gas-exchange and chlorophyll fluorescence, but only under continuous light. Aphid infestation under 72 h continuous dark was not associated with damage symptom formation or reduced photosynthetic metabolism.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The physiological and biochemical changes in wheat plants elicited by D. noxia feeding have been evaluated (Miller et al 1994;van der Westhuizen and Pretorius 1996;RaÞ et al 1996;Haile et al 1999;Ni et al 2001Ni et al , 2002Ni and Quisenberry 2003;Macedo et al 2003b). D. noxia usually feeds at the base of the youngest leaves of the plant, which is a strong sink for phloem-mobile mineral nutrients, amino compounds, and carbohydrates.…”
mentioning
confidence: 99%
“…The duration of infestation might be intimately linked with the biochemical and physiological response of wheat plants (Kriel et al 1986, Aalbersberg et al 1989, Hein et al 1989, Hein 1992, Macedo et al 2003b). In addition, previous studies demonstrated that although the mechanical injury pattern of different aphid species, such as D. noxia and R. padi, seems to be very similar, the salivary components in these species vary in composition, particularly oxido-reductases (catalase and peroxidase), which perhaps has a key role on injury-symptom development (i.e., leaf chlorosis) .…”
mentioning
confidence: 99%